Multifunctional performance of core–shell rGO@Fe3O4 on the mechanical, electrical/thermal, EMI, and microstructure properties of cement-based composites - Imanian Ghazanlou, Siamak; Imanian Ghazanlou, Siavash; Imanian Ghazanlou, Sroush; Karimi, Hamid; Azimi, Neda; Hosseinpour, Saman (Construction and Building Materials, 2023)
This research study focuses on the development of a multifunctional cement nanocomposite using reduced graphene oxide (rGO) nanosheets. To address the challenges of rGO dispersion, a core–shell structure of rGO@Fe3O4 (rGO@F) was investigated in cement paste. The rGO@F nanohybrid was thoroughly characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA). The main objectives of this study were to improve the mechanical properties, electrical conductivity, thermal conductivity, and chemical properties of the cement composite through the incorporation of rGO@F. The performance of the cement paste containing rGO0.1@Fe3O4 (0.1 wt% rGO and 1 wt% Fe3O4) was evaluated, and it was found that its toughness and compressive strength were significantly enhanced compared to the reference sample. Furthermore, the addition of rGO@F led to a remarkable increase in the electrical and thermal conductivity of the modified cement composite, attributed to the formation of conductive pathways facilitated by the rGO nanosheets. Comprehensive analyses including XRD, TGA, differential scanning calorimetry (DSC), thermally assisted microscopy (TAM), FTIR, and X-ray photoelectron spectroscopy (XPS) confirmed that the rGO@F nanohybrid had a significant impact on the chemical properties and hydration process of the hardened cement paste. SEM images revealed a more compact microstructure of the cement paste in the presence of rGO@F, demonstrating its role in crack inhibition. Additionally, an increase in the formation of improved hydration crystals such as tobermorite and jennite was observed. The core–shell structure of rGO@F exhibited exceptional electromagnetic wave absorption properties due to its layered configuration, effectively trapping the electromagnetic waves. Overall, this research study highlights the successful fabrication of a multifunctional cement nanocomposite through the incorporation of rGO@F. The findings demonstrate significant improvements in mechanical strength, electrical conductivity, thermal conductivity, chemical properties, crack inhibition, and electromagnetic wave absorption. This research contributes to the advancement of cement-based materials with enhanced performance and opens up avenues for various applications in fields such as construction, infrastructure, and telecommunications.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Cement; EMI wave shielding; Fe; Mechanical properties; rGO